2013
DOI: 10.1039/c2ob26535d
|View full text |Cite
|
Sign up to set email alerts
|

Investigations regarding the utility of prodigiosenes to treat leukemia

Abstract: Prodigiosenes, possessing a 4-methoxypyrrolyldipyrrin skeleton, are known for their anti-cancer activity. Structural modification of the C-ring resulted in a series of prodigiosenes that displayed promising activity against leukemia cell lines during in vitro analysis against the NCI 60 cancer cell line panel. Further in vivo studies of these compounds using the zebrafish model showed persistence of anti-leukemia properties in human K562 chronic myelogenous leukemia cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…The A and B pyrrole rings are directly connected, while the third ring is connected by a methyl bridge [3,4]. These components are synthesized by Gram-positive bacteria and Gram-negative bacteria, such as Pseudomonas, Vibrio, Streptomyces and Serratia, that have antimicrobial activity [5], anti-malarial activity [6,7], immunosuppressive activity [8][9][10], and antitumor activity [11][12][13]. Serratamolide was isolated for the first time in 1961 [14] from a Serratia marcescens.…”
Section: Introductionmentioning
confidence: 99%
“…The A and B pyrrole rings are directly connected, while the third ring is connected by a methyl bridge [3,4]. These components are synthesized by Gram-positive bacteria and Gram-negative bacteria, such as Pseudomonas, Vibrio, Streptomyces and Serratia, that have antimicrobial activity [5], anti-malarial activity [6,7], immunosuppressive activity [8][9][10], and antitumor activity [11][12][13]. Serratamolide was isolated for the first time in 1961 [14] from a Serratia marcescens.…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent zebrafish leukemia xenograft studies indicated that zebrafish are a useful animal model in cancer research and chemotherapeutic drug screening [48][50]. Several methods have been developed for the in vitro evaluation of cell proliferation (MTT assay), metastasis (under-agarose migration assay), and angiogenesis (endothelial tube formation assay).…”
Section: Discussionmentioning
confidence: 99%
“…K562 (an erythroleukemia from BCR-ABL1 + CML) and Jurkat (a PTEN -null, NOTCH1 -mutant T-ALL) were transplanted into embryos, and imatinib and cyclophosphamide responses were seen [89]. Similar findings were reported in a second study with imatinib and K562, and with all- trans -retinoic acid in NB4 (a PML-RARA + APML) [88], and then expanded further by testing investigational molecules against K562 in the same system [93]. If xeno-transplant can move beyond cell lines to include patient samples, “personalized medicine” assays could truly become viable.…”
Section: Research Applications Of Zebrafish Leukemia Modelsmentioning
confidence: 96%
“…Some of these molecules are in the pipeline for eventual clinical use, while others are reagents to inhibit key pathways, acting as surrogates for drugs with similar activity not yet developed. Human leukemic xeno-transplants have also been tested in fish [88, 89, 93]. Here, the biologic question is different: rather than testing agents for activity against the same type of leukemia from disparate species, the query is whether fish-based systems can provide templates for pre-clinical assays.…”
Section: Research Applications Of Zebrafish Leukemia Modelsmentioning
confidence: 99%